Pengaruh Sosialisasi Perpajakan, Reformasi Administrasi Perpajakan Dan Pengawasan Terhadap Kepatuhan Wajib Pajak Pada Kantor Pelayanan Pajak Perusahaan Masuk Bursa Daerah Khusus Jakarta - Mulyono; Akhmad Hidayat Rahadian (Jurnal Pajak Vokasi (JUPASI), 2026)
The compliance of taxpayer at the Public Listed Company Tax Office which reports on time is 80% of all 676 taxpayers. The socialization carried out 12 times a year still has not resulted in taxpayers complying with tax reports or implementing the rules that have been set. The aim of this research is to analyze the influence of tax socialization, tax administration reform, and individual and joint supervision on taxpayer compliance at the Public Listed Company Tax Office. The research uses quantitative method. The results of the study show (1) there is a positive and significant influence of tax socialization (X1) on taxpayer compliance (Y) which is 21%, meaning that taxpayer compliance can be influenced by the tax socialization variable, while the remaining 79% is caused by other factors. (2) There is a positive and significant influence of tax administration reform (X2) on taxpayer compliance (Y) which is 84.8%, meaning that taxpayer compliance can be influenced by the tax administration reform variable while the remaining 15.2% is caused by other factors. (3) There is a positive and significant influence of supervision (X3) on taxpayer compliance (Y) which is 60.1%, meaning that taxpayer compliance can be influenced by the supervision variable while the remaining 39.9% is caused by other factors. (4) There is a positive and significant influence of tax socialization (X1), tax administration reform (X2), and supervision (X3) together on taxpayer compliance (Y) which is classified as very strong. In addition, a determination coefficient value of 0.849 was obtained, meaning that the percentage of tax socialization, tax administration reform, and supervision variables can explain taxpayer compliance of 84.9% and the remaining 15.1% is influenced by other variables that are not included in the model. Keywords: Tax Socialization; Tax Administration Reform; Supervision and Compliance